Evaluation of pH variation and cervical dentin permeability in teeth submitted to bleaching treatment (Pesquisa Odontológica Brasileira, 2002)
External cervical root resorption is one of the disadvantages of the bleaching procedure. There are several mechanisms that may be responsible for causing resorption, such as the chemical and physical action of the utilized materials and the morphology of the cementoenamel junction. The purpose of this study was to investigate the presence of a communication between the pulp chamber and the external root surface. The investigation was carried out by means of pH tests and measurement of dye infiltration into cervical dentin after the bleaching procedure. Thirty-four human permanent incisors were submitted to endodontic treatment. The teeth were assigned to three experimental groups, according to the level at which the filling was cut, and to the sealing of the root canal entrance with glass ionomer cement. Sodium perborate and 30% hydrogen peroxide were utilized for bleaching. pH readings were carried out after 30 minutes, 24 h, 48 h and 72 h from the beginning of the procedure. The teeth were immersed in 0.5% basic fuchsin for 24 h in order to determine possible differences in the permeability of cervical dentin. The results revealed that pH tended to change when the root filling was cut at the entrance of the canal, when 2 mm of the filling were removed, and when the canal entrance was sealed with glass ionomer. Dentinal permeability increased in the three experimental groups, in comparison with the control group. These slight differences may suggest a communication between the pulp chamber and the external root surface.